PENGARUH PROFITABILITAS, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE - Agnes Yunita Sari; Hayu Wikan Kinasih (Faculty of Economic and Business Universitas STIKUBANK, 2021)
This analysis aims to obtain empirical evidence regarding the effect of profitability, leverage, and institutional ownership on tax avoidance in manufacturing companies listed on the IDX for the period 2017-2019. The independent variable uses profitability, leverage, and institutional ownership, while the dependent variable is tax avoidance. Data were obtained from the financial reports of 40 manufacturing companies listed on the IDX for three research periods, namely 2017 - 2019, so that 120 observations were obtained. To prove the influence of the independent variable on the dependent variable, multiple regression analysis was performed. The results of the analysis conducted found that profitability has an effect on tax avoidance, while leverage and institutional ownership have no effect on tax avoidance. Keywords: profitability, leverage, institutional ownership, tax avoidance.